Development and Usability Evaluation of Inventive and Repurposable Children’s Furniture - Zhi Yuan Phuah; Poh Kiat Ng; Chai Hua Tay; Boon Kian Lim; Kia Wai Liew; Peng Lean Chong (Inventions)
This study developed inventive and repurposable children’s furniture to improve functionality and extend product lifespan. Unlike typical cribs which serve a single purpose, the proposed design supports multiple functions: crib, cushioned chair, highchair, walker, toilet attachment, pull-up bar, and bed safety rail. Specific dimensions were established, and the correct material selections were made for the selected concept. This was finalised using Autodesk Inventor 2019 that was used for stress analysis, and material optimisation. Usability tests were conducted to compare the proposed invention with single-function products. These tests were discussed in terms of task completion time, space-saving ability, survey feedback, and a REBA of musculoskeletal risk. It was found that the proposed design could be repurposed in a shorter time and save more space. A majority of the survey participants agreed that it performed well in terms of repurposability, design, space-saving ability, usability, comfort, sustainability, and safety. Additionally, the proposed design is cheaper compared to single-function products. Thus, creating inventive and repurposable children’s furniture can contribute to reducing waste and extending the lifespan of children’s furniture through innovative, cost-effective design solutions.